2004
DOI: 10.4049/jimmunol.172.11.6846
|View full text |Cite
|
Sign up to set email alerts
|

TNF Influences Chemokine Expression of Macrophages In Vitro and That of CD11b+ Cells In Vivo during Mycobacterium tuberculosis Infection

Abstract: Granulomas, focal accumulations of immune cells, form in the lung during Mycobacterium tuberculosis infection. Chemokines, chemotactic cytokines, are logical candidates for inducing migration of T lymphocytes and monocytes to and within the lung. TNF influences chemokine expression in some models. TNF-deficient mice infected with M. tuberculosis are highly susceptible to disease, and granuloma formation is inhibited. Through in vitro assays, we demonstrate that neutralization of TNF in M. tuberculosis-infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
110
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 127 publications
(119 citation statements)
references
References 29 publications
5
110
1
Order By: Relevance
“…This equation includes a constant source (term 1) and natural death term (term 7) maintaining a homeostatic level of resting macrophages that would typically be present in a healthy immune system. During infection, resting macrophages are recruited to the site of infection in response to TNF [5], a process that is inhibited by IL-10 (term 5) [14], and are additionally recruited by chemokines produced by activated and infected macrophages (term 2) [5]. Term 6 accounts for the fact that in the presence of IFN-γ, macrophage activation occurs given a secondary signal from TNF or extracellular bacteria [18].…”
Section: The Role Of Macrophages During Infectionmentioning
confidence: 99%
“…This equation includes a constant source (term 1) and natural death term (term 7) maintaining a homeostatic level of resting macrophages that would typically be present in a healthy immune system. During infection, resting macrophages are recruited to the site of infection in response to TNF [5], a process that is inhibited by IL-10 (term 5) [14], and are additionally recruited by chemokines produced by activated and infected macrophages (term 2) [5]. Term 6 accounts for the fact that in the presence of IFN-γ, macrophage activation occurs given a secondary signal from TNF or extracellular bacteria [18].…”
Section: The Role Of Macrophages During Infectionmentioning
confidence: 99%
“…Mice were infected via the aerosol route and placed in a closed-air aerosolization system (In-Tox Products, Albuquerque, NM) to deliver the desired CFU (3,38). Inocula of about 50 to 200 CFU/lung were employed for the mouse studies presented here.…”
Section: Mycobacteria and Infection Of Micementioning
confidence: 99%
“…Tumor necrosis factor alpha (TNF-␣), a cytokine whose protean biological functions include the regulation of immune cell trafficking (35) and the mycobacterial granulomatous response (2,3,13,21,30), plays a significant role in the control of acute and chronic tuberculosis as well as Mycobacterium bovis BCG infection in the mouse (13,21,30,34). Recently, the relevance of TNF in the control of persistent human tuberculous infection has been demonstrated by epidemiological evidence that individuals treated with TNF blockade therapy for a variety of inflammatory diseases exhibit increased risks for the development of reactivation tuberculosis (20).…”
mentioning
confidence: 99%
“…Neutralization of TNFa by using antibody or TNFR1-deficient macrophages demonstrated that expression of certain chemokines (CXCL9/monokine induced by IFNg, CXCL10/IFN-inducible protein 10, CXCL11/IFN-inducible T cell chemoattractant, CCL5/ RANTES, and CCL2/MCP-1) after M. tuberculosis infection was dependent, at least in part, on TNFa. However, the lack of TNFa did not completely abrogate chemokine expression, indicating that there are other factors, induced as a result of infection, that stimulate chemokine production [39].…”
Section: Chemokines and Tuberculosismentioning
confidence: 94%
“…In mouse models, gene expression of CXC and CC chemokines has been detected in the lungs after M. tuberculosis infection [39]. CXCR3-deficient mice [40] have an impaired granuloma formation after aerosol infection with M. tuberculosis, although this effect is transient, occurring at the early stages of infection.…”
Section: Chemokines and Tuberculosismentioning
confidence: 99%